Pengaruh Social Media Marketing, dan Kualitas Produk Terhadap Minat Pembelian di Riders and Rules - Andriana Pratama; Donant Alananto Iskandar (Research and Community Service UNIVERSITAS KALBIS, 2025)
This research aims to examine and demonstrate the influence of Social media marketing and Product Quality on consumers’ Purchase intention toward Riders and Rules products. The study involves three main variables, namely Social media marketing as the first independent variable, Product Quality as the second independent variable, and Purchase intention as the dependent variable. A quantitative research method was employed to obtain measurable and objective results regarding the relationships among these variables. The sample consisted of 125 respondents who had previously viewed content posted on the Riders and Rules Instagram account. Respondents were selected using a purposive sampling technique, which is a type of non-probability sampling method, ensuring that participants met specific criteria relevant to the research objectives. Data collected from the respondents were analyzed using SPSS version 20. The findings indicate that Social media marketing has a significant positive influence on Purchase intention. Furthermore, Product Quality also has a significant positive influence on Purchase intention. These results suggest that effective social media marketing strategies and high product quality can enhance consumers’ intention to purchase Riders and Rules products.